2009
DOI: 10.1037/a0014694
|View full text |Cite
|
Sign up to set email alerts
|

Reporting practices in confirmatory factor analysis: An overview and some recommendations.

Abstract: Reporting practices in 194 confirmatory factor analysis studies (1,409 factor models) published in American Psychological Association journals from 1998 to 2006 were reviewed and compared with established reporting guidelines. Three research questions were addressed: (a) how do actual reporting practices compare with published guidelines? (b) how do researchers report model fit in light of divergent perspectives on the use of ancillary fit indices (e.g., L.-T. Hu & P. M. Bentler, 1999; H. W. Marsh, K.-T., Hau,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
1,268
2
76

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 1,766 publications
(1,368 citation statements)
references
References 73 publications
22
1,268
2
76
Order By: Relevance
“…This study sought to overcome the focus on the child's difficulties (behavior problems), and to investigate their potentials (social skills), using CFA methodologies, considered by Jackson et al (2009) as an indispensible statistical tool for studies associated with construct evidence, namely in the development of rating scales. In this sense, this study sought to validate the factor structure of the Portuguese version of the Social Skills scale of the PKBS-2 (Merrell, 2002a), with the difficulty and complexity of definition and conceptualization of the social skills construct, reported in the literature (Gresham, 1986;Merrell & Gimpel, 1998), eventually becoming apparent in the CFA studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study sought to overcome the focus on the child's difficulties (behavior problems), and to investigate their potentials (social skills), using CFA methodologies, considered by Jackson et al (2009) as an indispensible statistical tool for studies associated with construct evidence, namely in the development of rating scales. In this sense, this study sought to validate the factor structure of the Portuguese version of the Social Skills scale of the PKBS-2 (Merrell, 2002a), with the difficulty and complexity of definition and conceptualization of the social skills construct, reported in the literature (Gresham, 1986;Merrell & Gimpel, 1998), eventually becoming apparent in the CFA studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although considered a controversial practice and a target of debate in the scientific community, based on the under-representation of the model or the appropriateness of the use of normative data based on parcels (Little et al, 2002), the use of parcels in CFA studies has been increasingly implemented in this kind of research (Raimundo et al, 2012). Therefore, the most common method of estimation in the literature was used (Jackson et al, 2009), the maximum likelihood, and the procedures suggested in the PKBS-2 manual were followed, by testing the model fit not only for the entire sample but also for Figure 2. Confirmatory factor analysis of the Social Skills scale of the ECIP-2 (Final parcels model).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations